2021
DOI: 10.1101/2021.08.09.454968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global prediction of candidate R-loop binding and R-loop regulatory proteins

Abstract: In the past decade there has been a growing appreciation for R-loop structures as important regulators of the epigenome, telomere maintenance, DNA repair and replication. Given these numerous functions, dozens, or potentially hundreds, of proteins could serve as direct or indirect regulators of R-loop writing, reading, and erasing. In order to understand common properties shared amongst potential R-loop binding proteins (RLBPs) we mined published proteomic studies and distilled 10 features that were enriched i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 102 publications
(97 reference statements)
1
0
0
Order By: Relevance
“…Next, we used synthetic R-loops and pure MLH1 protein and detected the binding between R-loops and MLH1 by S9.6-mediated ChIP-IB (Figure 4E). Our findings are supported by a recent report that identified MLH1 as an R-loop-binding protein by a global prediction model (32). By in vitro nuclease assay, we observed that MLH1 degraded the RNA strand of R-loop structure with or without tails in a concentration-dependent manner (Figure 4F).…”
Section: Resultssupporting
confidence: 91%
“…Next, we used synthetic R-loops and pure MLH1 protein and detected the binding between R-loops and MLH1 by S9.6-mediated ChIP-IB (Figure 4E). Our findings are supported by a recent report that identified MLH1 as an R-loop-binding protein by a global prediction model (32). By in vitro nuclease assay, we observed that MLH1 degraded the RNA strand of R-loop structure with or without tails in a concentration-dependent manner (Figure 4F).…”
Section: Resultssupporting
confidence: 91%